Construction Management Research: A Comparison of Perceived Value by General Contractors, Prevalence of Publication, and Funding. Issue 3 (2nd July 2016) - Bigelow, Ben F.; Bilbo, David; Baker, Michele
ABSTRACT: This study identifies areas of research where future investigation can make the highest impact and contribute to the expansion of knowledge in the field of construction management. A disconnect between academia and the construction management [CM] industry often results in research that lacks value for the industry. The purpose of this research is to explore that disconnect and to identify research topics to guide CM faculty and graduate students towards research that is of the greatest value to the industry. A comprehensive review and a funding analysis of published research were conducted and the resulting data used to develop an in-depth questionnaire to guide interviews with members of the Texas A&M University Construction Industry Advisory Council (CIAC). Interviews were conducted as focus groups with CIAC members in Houston, Dallas, San Antonio, Austin, and surrounding areas. Topic rankings and specific themes emerged from the interviews. The results of the interviews were then compared to CM funded research, and the volume of published research. The results show that while there is a small degree of overlap, the top industry priorities do not align with research being funded or the majority of published literature.